90.3k views
0 votes
Please help me ASAP!!!!
30 points

Please help me ASAP!!!! 30 points-example-1
User Adanlif
by
4.7k points

1 Answer

1 vote

Answer:

37

Explanation:

f(x) = 2x-1

g(x) =x^2 +3

f°g(x) = means put g(x) in for x into the function f(x)

f(g(x)) = 2 (g(x)-1

=2(x^2 +3) -1

Distribute

= 2x^2 +6-1

=2x^2 +5

Now we let x=-4

f(g(-4)) = 2 (-4)^2 +5

=2(16) +5

=32+5

=37

User Sajan Chandran
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.